Distinct Hypnotic Recoveries After Infusions of Methoxycarbonyl Etomidate and Cyclopropyl Methoxycarbonyl Metomidate: The Role of the Metabolite. (April 2016) - Pejo, Ervin; Liu, Jifeng; Lin, Xiangjie; Raines, Douglas E.
Abstract : BACKGROUND: Methoxycarbonyl etomidate (MOC-etomidate) and cyclopropyl methoxycarbonyl metomidate (CPMM) are rapidly metabolized "soft" etomidate analogs. CPMM's duration of hypnotic effect is context insensitive, whereas MOC-etomidate's is not. In this study, we tested the hypothesis that CPMM's effect is context insensitive because, unlike MOC-etomidate, its metabolite fails to reach physiologically important concentrations in vivo even with prolonged continuous infusion. METHODS: We compared the potencies with which MOC-etomidate and CPMM activate α1 (L264T)β3 γ2 γ-aminobutyric acid type A receptors and induce loss-of-righting reflexes (i.e., produce hypnosis) in tadpoles with those of their metabolites (MOC-etomidate's carboxylic acid metabolite [MOC-ECA] and CPMM's carboxylic acid metabolite [CPMM-CA], respectively). We measured metabolite concentrations in the blood and cerebrospinal fluid of Sprague-Dawley rats on CPMM infusion and compared them with those achieved with MOC-etomidate infusion. We measured the rates with which brain tissue from Sprague-Dawley rats metabolize MOC-etomidate and CPMM. RESULTS: Both analogs and their metabolites enhanced γ-aminobutyric acid type A receptor function and induced loss-of-righting reflexes in a concentration-dependent manner. However, in these 2 assays, CPMM-CA's potency relative to its parent hypnotic was approximately 1:4900 and 1:1900, respectively, whereas MOC-ECA's was only approximately 1:415 and 1:390, respectively. With 2-hour CPMM infusions, CPMM-CA reached respective concentrations in the blood and cerebrospinal fluid that were 2 and >3 orders of magnitude lower than that which produced hypnosis. CPMM was metabolized by the brain tissue at a rate that is approximately 1/15th that of MOC-etomidate. CONCLUSIONS: Hypnotic recovery after CPMM administration is context insensitive because its metabolite does not accumulate to hypnotic levels in the central nervous system. This reflects the very large potency ratio between CPMM and CPMM-CA and the resistance of CPMM to metabolism by esterases present in the brain. Abstract : Published ahead of print January 25, 2016